Public Health Promotion: Autonomy of the Emergency Nurse Practitioner - Cheryl Ann Alexander; Lidong Wang (Intelektual Pustaka Media Utama, 2015)
The purpose of this paper is to examine several key issues in health care reform. From the Patient Protection and Affordable Care Act of 2010 to the cholera epidemic in Haiti, global health care reform is necessary to promote health and wellness among all nations. There is an international shortage of nurses and nursing faculty. Among the providers, it is also necessary to examine autonomy of the most up and coming nurse provider: the emergency nurse practitioner.